Association of Hypertension and Dyslipidemia in Young Adults - Raj, G. A Augustine; Reddy, Syam Sundar (Asian Journal of Medical Research, 2018)
Background: Dyslipidemia, characterized by abnormal levels of lipids in the blood, poses a significant public health concern worldwide due to its association with increased risk of cardiovascular diseases (CVDs). While dyslipidemia is commonly studied in older populations, its prevalence and impact among young adults have garnered increasing attention in recent years. Young adults with dyslipidemia often exhibit diverse lipid profiles, including elevated levels of low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), and decreased levels of high-density lipoprotein cholesterol (HDL-C). Such variations may be influenced by genetic predispositions, lifestyle factors, and underlying health conditions. Subjects and Methods: This prospective study was conducted in the Department of General Medicine, Narayana Medical College, Nellore. Young individuals with a diagnosis of dyslipidaemia and receiving treatment of dyslipidaemia and/or diabetes and/or hypertension, attending to hospitals and clinics in India. The inclusion criteria were patients of either sex, aged within the range of 18 - 45 years, with a confirmed diagnosis of dyslipidaemia and receiving treatment for dyslipidaemia and/or diabetes mellitus and/or hypertension. Patients aged >45 years were excluded. Results: In our study, we observed mean age as 37.23 years and mean weight of patients as 69.08 kg and mean height to be 165.35 cm, mean waist circumference as 84.06 cm and mean BMI to be 25.23 among studied cohort. We observed in our study that 189 (94.7%) patients were euthyroid while only 11 (5.3%) were hypothyroid. There was no significant correlation of PTCA among hypothyroid and euthyroid patients in this study seen. There was significant correlation of PTCA among patients with and without endothelial dysfunction in this study seen. There was significant correlation of PTCA among patients with and without statin use as inclusive factor in this study. Conclusion: In conclusion, this study provides valuable insights into the complex interplay of dyslipidemia, its risk factors, associated comorbidities, and cardiovascular manifestations in young adults. By examining the patterns of dyslipidemia and its relationship with various factors, including genetic predispositions, lifestyle habits, and medical conditions, we have gained a deeper understanding of the multifaceted nature of this condition in the younger population.